Pemantauan dan Evaluasi Aspek Kinerja Penyelenggaraan Pelayanan Publik pada Kecamatan Kenjeran Kota Surabaya - Ghea Arnanda; Rosyidatuzzahro Anisyukurillah (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Monitoring and Evaluation of Public Service Performance (PEKPPP) is the process of measuring public service performance in a work unit systematically within a predetermined period of time in accordance with regulations on performance appraisal guidelines, namely PermenPAN RB Number 5 of 2023. The purpose of this study was conducted to determine and analyze the extent to which the optimization of the implementation of public service performance in the locus unit of the Kenjeran District Office, Surabaya City. This research uses descriptive qualitative research with primary data collection techniques, namely interviews, field observations, and documentation, along with secondary data that the author gets through laws and regulations, books, articles, journals and publication sources relevant to the research. The results showed that Kenjeran Sub-district has implemented six aspects of good governance because it has compiled a governance policy document, published a Public Service Information System through printed media in the service room and the sub-district website / social media, there are facilities and infrastructure such as service rooms, parking areas, toilets, lactation rooms, wheelchairs, front offices (FO), complaints consultations and other supporting facilities that are easily accessible to service users and suitable for use, besides that there are innovations in Kenjeran Sub-district.